Metabolomics and Dual RNA-Sequencing on Root Nodules Revealed New Cellular Functions Controlled by Paraburkholderia phymatum NifA - Bellés-Sancho, Paula (Metabolites, 2021)
Paraburkholderia phymatum STM815 is a nitrogen-fixing endosymbiont that nodulate the agriculturally important Phaseolus vulgaris and several other host plants. We previously showed that the nodules induced by a STM815 mutant of the gene encoding the master regulator of nitrogen fixation NifA showed no nitrogenase activity (Fix(−)) and increased in number compared to P. vulgaris plants infected with the wild-type strain. To further investigate the role of NifA during symbiosis, nodules from P. phymatum wild-type and nifA mutants were collected and analyzed by metabolomics and dual RNA-Sequencing, allowing us to investigate both host and symbiont transcriptome. Using this approach, several metabolites’ changes could be assigned to bacterial or plant responses. While the amount of the C(4)-dicarboxylic acid succinate and of several amino acids was lower in Fix(−) nodules, the level of indole-acetamide (IAM) and brassinosteroids increased. Transcriptome analysis identified P. phymatum genes involved in transport of C(4)-dicarboxylic acids, carbon metabolism, auxin metabolism and stress response to be differentially expressed in absence of NifA. Furthermore, P. vulgaris genes involved in autoregulation of nodulation (AON) are repressed in nodules in absence of NifA potentially explaining the hypernodulation phenotype of the nifA mutant. These results and additional validation experiments suggest that P. phymatum STM815 NifA is not only important to control expression of nitrogenase and related enzymes but is also involved in regulating its own auxin production and stress response. Finally, our data indicate that P. vulgaris does sanction the nifA nodules by depleting the local carbon allocation rather than by mounting a strong systemic immune response to the Fix(−) rhizobia.